'A pair of buttocks' that everybody hates. (23rd December 2021) - Makoni, Busi
Abstract : This article explores radical rudeness, a resistance strategy of deliberate rudeness to disrupt normative structures. Using the Uganda activist Dr Stella Nyanzi as a case study, I examine how women experiencing extreme structural marginalisation and systemic violence use radical rudeness in a nonlinguistic form (defiant disrobing) to speak back to power. Drawing from Black feminist theories of rage, I argue that radical rudeness is an instance of rage, not as a pernicious emotion, but as a legitimate strategy against patriarchy and dictatorial authoritarianism. I argue that Dr Stella Nyanzi's naked protest utilises three intersecting forms of power – biopower, symbolic power and cosmological power – to resist the authoritarian Ugandan regime, turning her naked body into a powerful weapon of resistance.